The Analysis of Related Factors of Cervical Cancer Prevention Behavior in Reproductive-Aged Women - Adilla Kusuma Dewi; Mira Triharini; Tiyas Kusumaningrum (Pediomaternal Nursing Journal, 2019)
ABSTRACTIntroduction:  Cervical cancer is a disease which can causes and increase infertility, morbidity and mortality of women in the world. The incidence rates of cervical cancer can be reduced by doing primary and secondary preventions. This study aims to determine the relation of self-efficacy, perceived barriers and interpersonal factors to cervical cancer prevention behavior in reproductive-aged women.Method:  The study design was correlational study with cross sectional approach. The population were married women of reproductive-age between 15-45 years old in Pacarkeling community health center, Surabaya. The sample of this study was 110 respondents which used cluster sampling technique. The independent variables were perceived barriers, self-efficacy and interpersonal factors and the independent variable was cervical cancer prevention behavior. The data analyzed by using spearman rho statistical test with a significance level of α ≤ 0.05 to find out the related variables to the cervical cancer prevention behavior in reproductive-aged women.Result:  The results of this study shows that the perceived barriers (p = 0,000) and interpersonal factors (p = 0,001) were related to cervical cancer prevention behavior (α ≤ 0,05), however self-efficacy was not related to cervical cancer prevention behavior (p = 0,668).Conclusion: Perceived barriers and interpersonal factors could determine the cervical cancer prevention behavior in reproductive-aged women. However, self-efficacy was not proven to determine the cervical cancer prevention behavior. Further, most of women in this study have low self-efficacy, but they have good cervical cancer prevention behavior.